Model characteristics of the structure physical training fighters qualifications - Pryimakov O.O (Kharkov National Pedagogical University, 2013)
Studied the structure of the relationship of physical fitness level fighters with physical disabilities and special performance. It is studied 147 athletes Ukraine qualifications in Greco-Roman and freestyle wrestling, judo. Applied the methods of anthropometry kaliperometrii, teacher testing, testing of a special performance. It is shown that the qualification defines the relationship and the relationship of morphometric and speed-power performance, the level of special performance athletes. With the advanced training of fighters increased level of speed, force readiness, increase the size Spigot neck, hips, chest, shoulders, reduced the percentage of fat component, increases muscular component, the index increased muscle development. Morphometric parameters with the most skilled fighters and cross-linked Spigot size of the body of the speed and power - explosive power, strength and speed-strength endurance, speed.